A counterexample to Henry E. Dudeney’s star puzzle - A. V. Ravsky (Математичні Студії, 2021)
We found a solution of Henry E. Dudeney’s star puzzle (a path on a chessboard from c5 to d4 in 14 straight strokes) in 14 queen moves, which was claimed impossible by the puzzle author. Generalizing this result to other board sizes, we obtained bounds on minimal number of moves in a board filling queen path with given source and destination.